Perbedaan Perilaku Agresif Siswa ditinjau dari Keluarga Utuh dan Keluarga Bercerai - Nike Putri Rahayu; Afrizal Sano (CENDEKIA: Jurnal Ilmu Sosial, Bahasa dan Pendidikan, 2024)
This study aims to examine differences in students' aggressive behavior in terms of intact families and divorced families. This research uses quantitative research methods with a comparative study approach. The population in this study was 822 students in classes X and XI at SMK Negeri 9 Padang with a total sample of 355 students. The data collection technique uses an aggressive behavior instrument using a Likert model scale. Data were analyzed using descriptive statistical analysis techniques and difference test analysis (T-test). The research results show: (1) the aggressive behavior of students who come from intact families is included in the low category with a percentage of 53.49%, (2) the aggressive behavior of students who come from divorced families is included in the low category with a percentage of 79.38%, (3 ) there is a significant difference in students' aggressive behavior in terms of intact families and divorced families at SMK Negeri 9 Padang, where the t value is -13.410 with a Sig.(2 tailed) value obtained of 0.001 or <0.05. Based on the results of this research, guidance and counseling teachers can provide assistance with information services, individual counseling, group counseling and group guidance services in dealing with aggressive behavior in students.